A likely planet-induced gap in the disc around T Cha - Hendler, Nathanial P.; Pinilla, Paola; Pascucci, Ilaria; Pohl, Adriana; Mulders, Gijs; Henning, Thomas; Dong, Ruobing; Clarke, Cathie; Owen, James; Hollenbach, David (Monthly notices of the Royal Astronomical Society. Letters, 2018)
Abstract. We present high-resolution (0.11 × 0.06 arcsec2) 3 mm ALMA observations of the highly inclined transition disc around the star T Cha. Our continuum i
Advance access publication 2017 December 6
Gesehen am 24.09.2019